Variability of Body Morphometric Parameters of Dwarf Sheep of Djallonke Breed according to the Ecotype (North and South), Age and Type of Birth - ADJIBODE, A. Gabriel; TOUGAN, P. ULBAD; DAOUDA, Huggue; ZANNOU, M. SERGE; HANZEN, Christian; KOUTINHOUIN, G. BENOÎT (My University, 2016)
The study aims to determine morphometric parameters of North and South ecotypes of Djallonke sheep of Benin by age and type of birth. Data were collected from November 2013 to December 2015 on 462 sheeps of North ecotype and 599 of South ecotype. These data were analyzed with SAS software (2006). It appears that all morphometric traits depend on the ecotype of sheep except body length. Indeed, the sheep of North ecotype were heavier (P<0.001) than south ecotype sheep and had recorded the greater wither’s height (P<0.001) with the higher values of head length, shoulders width, hip length, tail length and cannon perimeter. Similarly, chest perimeter of sheep of North ecotype was 59.64 cm to 57.9 cm for South ecotype (P<0.05). The values of live weight, head length, body length, hip length, tail length and height at wither increased very significantly with the age of animals (P<0.001). The single born lambs weighed heavier than lambs born from twin, triple and quadruple litter size, and had the highest body length, shoulder width and wither’s height (P<0.01). As for correlations, from the cannon perimeter which is slightly and positively associated with live weight (r=0.12; P<0.05), weakly and positively associated with head length (r=0.16; P<0.01), the other measured morphometric parameters were strongly and positively associated with live weight (0.30 ≤ r ≤ 0.85; P<0.001) and head length (0.26≤ r ≤ 0.81; P<0.001). Therefore, selection based on one trait will improve the other traits as a correlated response.
Keywords: Benin; ecotype; Djallonke sheep; morphometric traits; variation